Conformational maps of human 20S proteasomes reveal PA28- and immuno-dependent inter-ring crosstalks - Jean Lesne (Nature Portfolio, 2020)
Immune cells express immunoproteasomes (i20S), which bind to specialized regulators, contain different catalytic subunits and generate immunogenic peptides. HDX-MS—based assessment of the differences between the conformational dynamics of standard and i20s reveals specific, allosteric changes in i20S and upon regulator binding.